Tatbiq al-Adawat an-Nahwiyah li an-Nathiqin bi Ghairi al-‘Arabiyah min Khilal al-Kitab Bulugh al-Maram - Wendy Morrizha Pritantoro (Postgraduate of IAIN Metro Lampung Indonesia, 2020)
This research is descriptive analysis, this study aims to propose methods of learning Al-adawatun Nahwiyah to the non-Arab students through the text in the book Bulugh al-Maram. The problem of this study is that most of the non-Arabic Arabic learners find it difficult to explain the meaning of Al-adawatun Nahwiyah, as well as its division, function of its position, its laws and their use. So this research is to provide the teaching of Al-Adawatun Nahwiyah for non-Arabic students through the hadiths contained in the book Bulughul maram and the function of Al-adawatun Nahwiyah, and this learning is expected to be able to provide solutions in understanding Arabic texts. And after the researcher analyzes this research, it can be concluded that understanding the aims of the words of the Arabs, because of the different types of writing, and the goals of the style of language from religious texts must know the meanings of Al-Adawatun Nahwiyah, because actually Al-Adawatun Nahwiyah is one of the most important parts of the Arabic language, because Al-Adawatun Nahwiyah has an accurate meaning and many uses.